A review on the dominating factor for the conductivity enhancement of PEDOTs: The affinity of polyanion shell toward post-processing reagents?. (24th January 2023) - Song, Yueyi; Tang, Jingming; Qi, Yuxuan; Zhang, Jiawei; Li, Yuda; Wang, Feng
Abstract: 'Post-processing' is a frequently employed strategy to drive the high electrical performance of poly(3, 4-ethylenedioxythiophene) (PEDOT) conducting polymers (CPs). However, researchers have paid little attention to the influence of the polyanion-rich part (the shell of CP matrix) on the penetration kenetics of post-processing. Herein, based on a series of CPs with same PEDOT polymerization degrees, we demonstrate that increasing the molecular weight of poly(styrenesulfonic acid) (PSS) polyanion is capable of enhancing the affinity of polyanion-rich part toward post-processing reagents, thus enabling the reagents to penetrate through the polyanion shell more easily and inducing a more significant molecular re-arrangement and nanophase segregation between PEDOTs and polyanions. With increasing the PSS molecular weight from 70 to 1000 KDa, the conductivity of pristine CP film exhibits only a mild variation of about 0.23 S/cm (by a factor of 5.7%). In sharp contrast, the conductivity of H2 SO4 post-processed CP film boosts from about 400 to near 1400 S/cm, i. e. the post-processing efficacy is scaled up by 235%. This study provides a new perspective for the advancement of highly conductive CPs. Graphical abstract: Image 1 Highlights: A new prospective for the investigation of the famous post-pressing technique in PEDOTs is offered. Raising Mw is effective to enhance the affinity of polyanion shell of PEDOT matrixes toward post-processing reagents. The efficacy of post-processing can be scaled up by 235% with polyanion shell Mw /size effect.